2019
DOI: 10.1038/s41438-019-0207-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SlOFP20 affects floral organ and pollen development

Abstract: The OVATE gene was initially identified in tomato and serves as a key regulator of fruit shape. There are 31 OFP members in the tomato genome. However, their roles in tomato growth and reproductive development are largely unknown. Here, we cloned the OFP transcription factor SlOFP20. Tomato plants overexpressing SlOFP20 displayed several phenotypic defects, including an altered floral architecture and fruit shape and reduced male fertility. SlOFP20 overexpression altered the expression levels of some brassinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Additionally, it has been illustrated that SlOFP20 may play an important role in the crosstalk between BR and GA (Zhou et al, 2019). Interestingly, the present study showed that the transcripts of PtOFP8 and PtOFP14 were increased after treated with SA and MeJA, implying that these two PtOFP proteins may be involved in the crosstalk between SA and MeJA (Figure 4).…”
Section: Ptofp Genes Play Crucial Roles In Response To Phytohormonesupporting
confidence: 54%
“…Additionally, it has been illustrated that SlOFP20 may play an important role in the crosstalk between BR and GA (Zhou et al, 2019). Interestingly, the present study showed that the transcripts of PtOFP8 and PtOFP14 were increased after treated with SA and MeJA, implying that these two PtOFP proteins may be involved in the crosstalk between SA and MeJA (Figure 4).…”
Section: Ptofp Genes Play Crucial Roles In Response To Phytohormonesupporting
confidence: 54%
“…In this study, two miR827 members were significantly downregulated in response to MC ( Figure 3 and Supplementary Table 5 ), and miR827 was predicted to target the transcription repressor OVATE family protein (OFP1, Gh_D10G1150) ( Supplementary Table 6 ). Overexpression of OFPs in Arabidopsis, rice, and tomato has been reported to inhibit cell elongation and reduce plant height by suppressing GA biosynthesis ( Wang et al, 2007 ; Schmitz et al, 2015 ; Zhou et al, 2019 ). Thus, we speculate that the suppressed expression of miR827 by MC may lead to the accumulation of OFP1 and further reduce GA content, resulting in the inhibition of internode elongation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a deletion in the upstream regulatory region of SlOFP20 underlying a suppressor of ovate (sov1) locus is responsible for the elongated shape in the OVATE null mutation background (Wu et al 2018). The over-expression (OE) of SlOFP20 causes the production of rounder fruits in 'Yellow Pear' (Wu et al 2018) and flat/ oblate in 'Alisa Craig' (albeit, only one line is shown) (Zhou et al 2019). Consistent with this, Zhou et al (2021), Guo et al (2020) and Guan et al (2021) found a significant upregulation of PpOFP1 in flat fruits at early stages of development comparing several flat and round cultivars.…”
Section: Searching For the Candidate Gene Variantmentioning
confidence: 99%